1966
DOI: 10.3109/00016486609127052
|View full text |Cite
|
Sign up to set email alerts
|

The Action of Hormones on Juvenile Nasopharyngeal Angiofibroma

Abstract: A case of juvenile nasopliaryngeal angiofibronia trcatcd preoperatively first w i t h antlrogcii and then writ11 estrogen is rcported. I;nder androgeii therapy tlic tumor appe:n-cd to enlarge sonicwliat. T h i s w a s followed h y ;I conrse o f estrogen tlicrapy wliicli rcsultctl in a prompt and d r n i~i a t i c involution antl decrease i n size o f the tumor. It became w r y firni antl permitted cv~rlsioii with a iiiiniiiial ((i00 c c ) blood loss for this type of tunlor. Thc response of this tnnior to cstro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
2

Year Published

1971
1971
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 7 publications
0
25
1
2
Order By: Relevance
“…24,26,29,30 Schiff, 20 studying 4 cases, proposed that JNA may develop due to excess of androgen and reported tumor reduction following treatment with estrogen. Johnsen et al, 22 studying 1 case, and Johns et al, 23 studying 6 cases, also found a decrease in tumor size with estrogen treatment. Using electron microscopy, Kuttner et al 31 observed histological and cytological alterations of the vascular component and stromal fibroblasts in 4 patients treated with estrogen, suggesting a direct action of the hormone.…”
Section: Steroid Hormones and Nuclear Receptorsmentioning
confidence: 92%
See 1 more Smart Citation
“…24,26,29,30 Schiff, 20 studying 4 cases, proposed that JNA may develop due to excess of androgen and reported tumor reduction following treatment with estrogen. Johnsen et al, 22 studying 1 case, and Johns et al, 23 studying 6 cases, also found a decrease in tumor size with estrogen treatment. Using electron microscopy, Kuttner et al 31 observed histological and cytological alterations of the vascular component and stromal fibroblasts in 4 patients treated with estrogen, suggesting a direct action of the hormone.…”
Section: Steroid Hormones and Nuclear Receptorsmentioning
confidence: 92%
“…20 Initial studies focused on sex hormone imbalances as a potential mediator of JNA development. [20][21][22][23] Other studies have focused on the presence of sex hormone receptors in JNA tissue. 1,[23][24][25][26][27][28] The first evidence for an association between steroid hormone imbalance and JNA development was the observation that patients with JNA are sexually underdeveloped, and that tumor regresses only after full development of secondary sex characteristics.…”
Section: Steroid Hormones and Nuclear Receptorsmentioning
confidence: 99%
“…The literature, however, does note the association between surgical blood loss and JNA tumor size, 28 and also that hormonal treatment with estrogen leads to histological maturation of the vascular endothelium in JNA. 1 In conclusion, this study has demonstrated the safety and the beneficial impact of a 6-week course of flutamide on JNA and further clarified that the degree of tumor regression is correlated with serum testosterone levels and is mainly limited to patients that have attained puberty. Presurgical adjuvant treatment with flutamide can facilitate surgical excision and limit surgical morbidity.…”
Section: Discussionmentioning
confidence: 90%
“…[1][2][3] Diethylstilbesterol, an estrogen analog, was previously used to bring about tumor regression, 2,3 although it is not part of current practice because of its feminizing effects and a perceived risk of cardiovascular disease. Further, estrogen treatment led to suppression of gonadotropin release by the pituitary and consequent suppression of testosterone secretion; it remains unclear as to whether the effect of estrogen was by a direct action on the tumor or secondary to the decrease in gonadotropin and testosterone levels.…”
mentioning
confidence: 99%
“…Clinical studies have demonstrated tumor enlargement with the administration of testosterone and shrinkage with estrogen therapy [20]. Flutamide (2-methyl-n-[4-nitro-3{trifluoromethyl}phenyl]propanamide), is an orally active non-steroidal androgen antagonist (NSAA).…”
Section: Hormonal Therapymentioning
confidence: 99%